2022
DOI: 10.3390/s22134913
|View full text |Cite
|
Sign up to set email alerts
|

A New Immersive Virtual Reality Station for Cardiopulmonary Resuscitation Objective Structured Clinical Exam Evaluation

Abstract: The Objective Structured Clinical Exam (OSCE) is an assessment tool used as a reliable method for clinical competence evaluation of students. This paper presents an investigation focused on the chain of survival, its related exploration, management, and technical skills, and how Virtual Reality (VR) can be used for the creation of immersive environments capable of evaluating students’ performance while applying the correct protocols. In particular, the Cardiopulmonary Resuscitation (CPR) procedure is studied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…There were included 15 studies (Table 1 ) published between 2013 and 2023 and conducted in Europe [ 18 , 19 , 27 29 ], in North America [ 20 , 24 , 25 , 31 ], in Africa [ 32 , 33 ], in Asia [ 26 , 30 ], and in Central America [ 23 ]; one study did not report the country [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were included 15 studies (Table 1 ) published between 2013 and 2023 and conducted in Europe [ 18 , 19 , 27 29 ], in North America [ 20 , 24 , 25 , 31 ], in Africa [ 32 , 33 ], in Asia [ 26 , 30 ], and in Central America [ 23 ]; one study did not report the country [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of mistakes per patient case were comparable for both groups: control group 2 (0.8–3.3) versus VR group 2 (1–2) Most participants (76%) learned a lot from the CPVR-sim, and the simulation helped most (72%) of the participants remember the steps required in a CPR situation. Most enjoyed the CPVR-sim (86%), and using VR simulations for learning purposes (86%) The software was easy to use (72%) and quick to learn (93%), without needing written instructions (79%) Rodríguez-Matesanz et al [ 19 ] 2022 Madrid, Spain To highlight the limitations of traditional methods using mechanical manikins and the benefits of the new approaches that involve the students in virtual, immersive, and dynamic environments Cross-sectional study Basic CPR ND ND Convenience sampling 33 participants: 15 HCPs, 10 medical students, 6 professors and 2 traditional objective structured clinical exam examiners, from different nationalities 45.5% participants never tested a VR application before Age: 19 to 57 years Female: ND Hospital CPR-OSCE VR is a software application that can be executed both on PC or with Oculus Quest It featured multiple scripts to visualize the different environment props and characters, track the user’s location, movement and interaction, and measure the accuracy of the CPR performance The system can be used both with and without an external physical manikin and the extra tracking devices but in this study they were used Performance metrics are generated during the simulation. The user is assisted by an external manikin that provides a point of reference in the simulation, as well as tactile feedback Not performed All participants played the same scenario Sensors for automatic detection of participant performance After the simulation a questionnaire was administrated, and regarded: (1) personal data; (2) previous experience with VR, similar technologies, and objective structured clinical exam; (3) user experience with CPR-OSCE VR; and (4) fidelity of CPR-OSCE VR 88% of the participants obtained a correct compression rate, and 65% a positive outcome in the appropriated compression depth applied to the manikin A good level of realism was present for 97% of the participants Sadeghi et al [ 28 ] 2022 Netherlands To assess the feasibility and to establish the face and content validity of two clinical scenarios (shockable and not shockable CA) of the CPVR-sim Cross-sectional study Advanced CPR ND ND Convenience sampling 41 participants: 14 cardiothoracic surgeons, 5 residents, 12 junior physicians, 6 nurse practitioners, 4 medical students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is already some evidence from other work demonstrating validity and discriminative power of such approaches: Assessment of emergency medical skills based on VR 360° videos has yielded valid results across different levels of prior experience [14]. Additionally, the application of VR for assessing the effectiveness of resuscitation measures was considered realistic and valid by a larger group of experienced OSCE examiners [13]. We recently demonstrated that the di culty of a VR-based OSCE station was comparable to an analog station and the discriminative power regarding an entire curricular OSCE was even slightly superior [12].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality (VR) provides an immersive environment which enables trainees to explore and interact simulated accidents in a safe and controlled environment. Several recent studies attempted to investigate the impact of VR adoption on the CPR training effectiveness (Everson et al , 2021; Rodríguez-Matesanz et al , 2022; Yang et al , 2020). Barsom et al (2020) compared the CPR training performance between the standard protocol (using video) and the VR-enhanced protocol in a high school setting with 40 students.…”
Section: Discussionmentioning
confidence: 99%